1991
DOI: 10.1126/science.254.5039.1768
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Isomerism: Isolation of C 2 v ,-C 78 and D 3 -C 78

Abstract: Early reports on the formation of the higher fullerenes C(76), C(78), C(84), C(90), and C(94) by resistive heating of graphite stimulated theoretical calculations of possible cage structures for these all-carbon molecules. Among the five fullerene structures with isolated pentagons found for C(78), a closed-shell D3h-isomer was predicted to form preferentially. Two distinct C(78)-isomers were formed in a ratio of approximately 5:1 and could be separated by high-performance liquid chromatography. The carbon-13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
168
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(181 citation statements)
references
References 21 publications
11
168
0
2
Order By: Relevance
“…The final transposition of 5-and 6-membered rings from 32 to 17, on the other hand, simply represents a special case of the acenaphthylene bond-switch rearrangement already discussed (cf: Scheme 12). It is interesting to note, with respect to fullerene chemistry, that the 32 -> 17 transformation can be viewed as an "annealing mechanism" by which this tetracyclic C14l-I~ system can satisfy the "isolated pentagon rule" (36,37,38) (39,40). These authors have actually suggested a more circuitous mechanistic pathway from 33 to 34, but the evidence is equally compatible with the one-step isomerization in Scheme 18.…”
Section: (23)mentioning
confidence: 99%
“…The final transposition of 5-and 6-membered rings from 32 to 17, on the other hand, simply represents a special case of the acenaphthylene bond-switch rearrangement already discussed (cf: Scheme 12). It is interesting to note, with respect to fullerene chemistry, that the 32 -> 17 transformation can be viewed as an "annealing mechanism" by which this tetracyclic C14l-I~ system can satisfy the "isolated pentagon rule" (36,37,38) (39,40). These authors have actually suggested a more circuitous mechanistic pathway from 33 to 34, but the evidence is equally compatible with the one-step isomerization in Scheme 18.…”
Section: (23)mentioning
confidence: 99%
“…The D 3h -C 78 (4) isomer possesses the lowest stability; it has never been found in the fullerene soot. These differences are satisfactorily explained by the differences in the relative formation energies of the C 78 (1) -C 78 (5) isomers [3].…”
Section: Introductionmentioning
confidence: 60%
“…The abundances of C 78 (1) -C 78 (3) isomers in the fullerene soot are comparable, being dependent on the method of fullerene synthesis [3,4]. The D 3 -C 78 (1) and C 2v -C 78 (2) isomers were isolated chromatographically and their cage structures were confirmed by 13 C NMR spectroscopy [3]. At the same time, isomer D 3h -C 78 (5) is elusive because of a small band gap resulting in a very low solubility; its presence in the fullerene soot could be unambiguously confirmed by the structural study of a CF 3 derivative, C 78 (5)(CF 3 ) 12 [5].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Besides CgQ, larger fuUerene clusters can also be isolated from the soot [42,43,44,45,46], but the structures of many of these large fuUerenes are stiU not clear.…”
mentioning
confidence: 99%